2015
DOI: 10.1088/0952-4746/35/2/271
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of utilizing active personal dosimeters worn on the chest to estimate occupational eye lens dose in x-ray angiography

Abstract: The International Commission on Radiological Protection (ICRP) has recommended that the occupational dose limit to the eye lens be substantially reduced. To ensure compliance with these recommendations, monitoring of the occupational eye lens dose is essential in certain hospital work environments. For assessment of the eye lens dose it is recommended to use a supplementary dosimeter placed at a position adjacent to the eye(s). Wearing a dosimeter at eye level can, however, be impractical and distributing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
4
19
1
Order By: Relevance
“…This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (2013), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, 2015;Rigatelli et al, 2016).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (2013), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, 2015;Rigatelli et al, 2016).…”
Section: Discussioncontrasting
confidence: 88%
“…It has been reported that staff height may also influence occupational dose as the taller the staff member is, the further away their head is from the source of scattered radiation (Principi et al, ). This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, ; Rigatelli et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…The importance of careful positioning of the movable ceiling mounted lead shield has been previously reported especially when using biplane equipment, and this was echoed in the reviewed literature . Several authors declared the absence of ceiling and table‐mounted lead shields when no other additional lead protection such as lead glasses or skull caps were worn by staff .…”
Section: Methodsmentioning
confidence: 98%
“…Some authors investigated dose in relation to proximity to the x‐ray tube . Explanatory diagrammatic representation of the position of staff was provided in several articles which allows comparison by dosimetric location rather than assigned role. Specific articulation of staff distances from the x‐ray tube or table was constructive when comparing occupational doses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation